Diversity of Meloidogyne spp. in Nepalese Vegetable Cultivation, with Notes on their Economic Importance (Indian Journal of Nematology, 2025)
Root-knot nematodes (RKNs) are significant plant parasitic nematodes that impact the quantity and quality of numerous annual and perennial crops throughout the tropics and subtropics. The main goal of this study was to evaluate the prevalence and species diversity of RKNs in Nepal utilizing both morphological and molecular analysis. The samples were collected from vegetable growing areas of six districts of Nepal namely, Kathmandu, Lalitpur, Bhaktapur and Kavrepalanchok in the mid-hills, and Sunsari and Morang in the plains. Our results showed that the overall prevalence of RKNs was 75 per cent. The most prevalent Meloidogyne sp. found in both the regions was M. incognita, followed by M. javanica. This study presents compelling evidence of the significant prevalence and frequency of Meloidogyne spp. in Nepal, underscoring the urgent need to adopt effective management practices for these nematodes.